Energy efficiency in the building sector: a combined middle-out and practice theory approach - Reindl, Katharina; Palm, Jenny (International Journal of Sustainable Energy Planning and Management, 2020)
The building sector in Sweden and Europe is a major energy consumer, accounting for around 40% of total energy use. It is a challenge to optimize available technical and social strategies for the fragmented construction industry. Professionals such as architects and different building engineers play a crucial role in the technology adoption process. This study aims to contribute to the understanding of how and why energy efficiency and saving measures are implemented by different professionals. The paper combines perspectives focusing the “the middle” in an organisation and social practice theory (SPT) to develop a framework which can be used to enhance the understanding of how and why energy efficiency measures are adopted in building processes. By combining these theoretical perspectives it is possible to arrive at a deeper understanding of what needs to be changed in the planning and management process to achieve a highly energy efficient renovation.